Discussion in 'Homework Help' started by zelda1850, Nov 13, 2010.

1. ### zelda1850 Thread Starter New Member

Jan 3, 2010
18
0
am i doing these questions correctly can someone check

1) 3$\sqrt{3}$(4-3$\sqrt{5}$)

3$\sqrt{3}$ * (4) = 12$\sqrt{3}$
3$\sqrt{3}$ * (3$\sqrt{5}$ = 9$\sqrt{15}$)

= 12$\sqrt{3}$ - 9$\sqrt{15}$

2) 4$\sqrt{15}$(-3$\sqrt{6}$ + 5)

4$\sqrt{15}$ * (-3$\sqrt{6}$ = 12$\sqrt{90}$)
4$\sqrt{15}$ * (5) = 20$\sqrt{15}$

12$\sqrt{90}$ + 20$\sqrt{15}$

3) $\sqrt{-2}$ ($\sqrt{10}$ - 4$\sqrt{6}$

$\sqrt{-2}$ * $\sqrt{10}$ = $\sqrt{-20}$
$\sqrt{-2}$ * 4$\sqrt{6}$ = 4$\sqrt{-12}$

= $\sqrt{-20}$ - 4$\sqrt{-12}$

4) ($\sqrt{2a}$ - 5)(7$\sqrt{2a}$ - 5)

-5 * -5 = -25
-5 * $\sqrt{2a}$ = -10a

7$\sqrt{2a}$ * -5 = -35 $\sqrt{2a}$
7$\sqrt{2a}$ * 2a = 7$\sqrt{2a}$

and then i got stuck

5) (7+ $\sqrt{6}$)(1 + $\sqrt{6}$)

$\sqrt{6}$ * $\sqrt{6}$ = $\sqrt{36}$
$\sqrt{6}$ * 7 = 7$\sqrt{-12}$

1 * $\sqrt{6}$ = $\sqrt{6}$
1 * 7 = 7

= 7 + 7$\sqrt{6}$ + $\sqrt{36}$

Last edited: Nov 13, 2010
2. ### mik3 Senior Member

Feb 4, 2008
4,846
67
1) correct

2) sign error

3) correct

4) wrong

5) wrong